(untitled) (Journal of Comparative Social Work, 2009)
In this article, the challenges of carrying out life story interview research on the adult sons of problem-drinking fathers will be discussed. Earlier studies have shown that parents’ problem drinking can disturb family life and be harmful in various ways to children. In the case of a problem-drinking father and his son, aspects of the father-son relationship and of the father as a male role model also assume major importance. Consequently, fathers’ drinking may continue to be a sensitive and a painful topic for their sons in adulthood. Moreover, several studies indicate that recruiting young men as a focus group for interview study is complicated. In addition, family matters are often perceived as something private, not to be talked about or shared with outsiders.For these reasons the life story interview method can be problematic for the researcher interested in collecting and interpreting interview data on sons’ childhood experiences. In my study, both finding interviewees, carrying out interviews on a sensitive topic and interpreting the data “truthfully” were challenging tasks presenting a number of ethical considerations. The data used in the study consist of 21 life story interviews with young Finnish men aged 21-42. While these young men were growing up, their fathers were problem drinkers. In the interviews the young men produced narratives or stories about their lives from an adult perspective. Thus narrative analysis is suggested to be applied in analysing the interviews.